2018
DOI: 10.3390/app8101872
|View full text |Cite
|
Sign up to set email alerts
|

Different Soil Particle-Size Classification Systems for Calculating Volume Fractal Dimension—A Case Study of Pinus sylvestris var. Mongolica in Mu Us Sandy Land, China

Abstract: Characterizing changes in the soil particle-size distributions (PSD) are a major issue in environmental research because it has a great impact on soil properties, soil management, and desertification. To date, the use of soil volume fractal dimension (D) is a feasible approach to describe PSD, and its calculation is mainly dependent on subdivisions of clay, silt, sand fractions as well as different soil particle-size classification (PSC) systems. But few studies have developed appropriate research works on how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…For different vegetation types in the same area, such as the Hulunbuir sands, the four vegetation species differed greatly, indicating that the selection of shrub species still needs to be analyzed and compared with the actual conditions and suitability of each area. Studies on different vegetation covers showed that when the vegetation cover was low (<15%), the area was in a more serious stage of land desertification, and the silt-clay content was below 10% [47,[63][64][65][66][67]. With the increase in vegetation cover, the silt-clay content gradually increased to 20-25% at a more moderate rate, indicating that the effect of the initial vegetation establishment on the silt-clay particle content was not significant.…”
Section: Biological Sand Fixation Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…For different vegetation types in the same area, such as the Hulunbuir sands, the four vegetation species differed greatly, indicating that the selection of shrub species still needs to be analyzed and compared with the actual conditions and suitability of each area. Studies on different vegetation covers showed that when the vegetation cover was low (<15%), the area was in a more serious stage of land desertification, and the silt-clay content was below 10% [47,[63][64][65][66][67]. With the increase in vegetation cover, the silt-clay content gradually increased to 20-25% at a more moderate rate, indicating that the effect of the initial vegetation establishment on the silt-clay particle content was not significant.…”
Section: Biological Sand Fixation Measuresmentioning
confidence: 99%
“…Different coverage of vegetation and silt-clay content (Data from reference[47,[63][64][65][66][67]). …”
mentioning
confidence: 99%
“…The seventh digit specifies one of five categories of soil texture [21]. Of the available physical, hydro-physical and chemical soil properties observed during the survey, only the soil types according to soil texture (based on Novák's classification adapted from the Kachinski system [23][24][25]) were "projected" into mapping and included in ESEUs. However, the informative value of those datasets is decreasing, as updates are elaborated only in terms of the definition of agricultural land (by drawing possible changes in the forest boundary) and slope conditions processed by geodetic activity in the landscaping process [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Under various circumstances, frequency-size distribution of fractures, faults, mineral deposits, oilfields, earthquakes, and topography can be represented by the concept of fractals [8]. Some studies have reported the use of a fractal-based model in the geology to investigate relationships between the properties of pore structure, soil, and FD in different locations, such as tight sandstone and mudstone [18][19][20]. Gong et al [21] utilized a FD-based method to describe and predict the complex natural fractures in the tight conglomerate reservoirs.…”
Section: Introductionmentioning
confidence: 99%